DO FINANCIAL RATIOS, FIRM CHARACTERISTICS AND CORPORATE GOVERNANCE AFFECT FIRM PERFORMANCE? - JENNY JENNY; SILVY CHRISTINA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2018)
The purpose of this research is to provide evidence about variables that influence firm performance. These variables are board size, debt ratio, firm size, firm age, return on asset, and independent board. Sample of this research are 67 manufactured companies listed in Indonesia Stock Exchange. The sample selected using purposive method, during the 2013 until 2015. Hypothesis tested by using multiple regression analysis. In this research, firm performance were measured by Tobin’s Q. The result of this research shows that debt ratio, firm size, return on asset and independent board have influence on firm performance. The other variables such as board size and firm age have no influence on firm performance.